Dampak Kebijakan Investasi dan Perdagangan Kayu Bulat terhadap Kinerja Hutan Taman Industri di Indonesia - Rukmantara, Rukmantara (Surya Octagon Interdisciplinary Journal of Science and Technology, 2015)
The objective of the research is to comprehend the effect of investment and trade policies on forest plantation investment development in Indonesia.  In 1990 the government issued Forest Plantation (HTI) policy which aimed at accelerating the growth of HTI investment. However the change of economy and political circumstances in 1997/1998 has led to the change of investment policies on HTI such as discontinued access on Government investment facilities and interest free of loan, a continue forest clearing for HTI, and ban on roundwood export.  Those policies were the source of  market competitiveness to fall and further discouraged HTI investment developmment. The research recommends to reform current policies by combining to open round wood export and provide soft loan followed by termination of forest clearing (conversion natural forest to HTI area) policy.  By this approach, the government has great opportunity to accelerate investment growth on forest plantation, increase economic- financial efficiency, and socio economic benefits.